Clinical course of COVID‐19 in a liver transplant recipient on hemodialysis and response to tocilizumab therapy: A case report. Issue 8 (3rd June 2020) - Hammami, Muhammad Baraa; Garibaldi, Brian; Shah, Pali; Liu, Gigi; Jain, Tania; Chen, Po‐Hung; Kim, Amy K.; Avdic, Edina; Petty, Brent; Strout, Sara; Fine, Derek M.; Niranjan‐Azadi, Ashwini; et al.
Abstract : The novel coronavirus disease 2019 (COVID‐19) is a highly infectious and rapidly spreading disease. There are limited published data on the epidemiology and outcomes of COVID‐19 infection among organ transplant recipients. After initial flulike symptoms, progression to an inflammatory phase may occur, characterized by cytokine release rapidly leading to respiratory and multiorgan failure. We report the clinical course and management of a liver transplant recipient on hemodialysis, who presented with COVID‐19 pneumonia, and despite completing a 5‐day course of hydroxychloroquine, later developed marked inflammatory manifestations with rapid improvement after administration of off‐label, single‐dose tocilizumab. We also highlight the role of lung ultrasonography in early diagnosis of the inflammatory phase of COVID‐19. Future investigation of the effects of immunomodulators among transplant recipients with COVID‐19 infection will be important. Abstract : This study reports the clinical course and management of a liver transplant recipient with COVID‐19 pneumonia who later developed marked inflammatory manifestations with rapid improvement after administration of off‐label, single‐dose tocilizumab.